Three‐dimensional skeletal mandibular changes associated with Herbst appliance treatment. (May 2017) - Souki, B. Q.; Vilefort, P. L. C.; Oliveira, D. D.; Andrade, I.; Ruellas, A. C.; Yatabe, M. S.; Nguyen, T.; Franchi, L.; McNamara, J. A.; Cevidanes, L. H. S.
Abstract : Objectives: Three‐dimensional evaluation of skeletal mandibular changes following Herbst appliance treatment. Setting and Sample Population: Retrospective case–control study, based on a sample size calculation. Twenty‐five pubertal patients treated with Herbst appliance (HAG), and 25 matched Class II patients who received other non‐orthopaedic dental treatments (CG). Material and Methods: Three‐dimensional models were generated from pre‐treatment (T0) and post‐treatment (T1) cone beam computed tomograms. Volumetric registration on the cranial base was used to assess mandibular displacement; volumetric regional registration was performed to evaluate mandibular growth. Quantitative measurements of X, Y, Z and 3D Euclidian changes, and also qualitative visualization by colour‐mapping and semi‐transparent overlays were obtained. Results: Downward displacement of the mandible was observed in both HAG and CG (2.4 mm and 1.5 mm, respectively). Significant forward displacement of the mandible was observed in the HAG (1.7 mm). HAG showed greater 3D superior and posterior condylar growth than the CG (3.5 mm and 2.0 mm, respectively). Greater posterior growth of the ramus was noted in the HAG than in CG. Conclusions: Immediately after Herbst therapy, a significant mandibular forward displacement was achieved, due to increased bone remodelling of the condyles and rami compared to a comparison group. Three‐dimensional changes in the direction and magnitude of condylar growth were observed in Herbst patients.